Mekanisme Pembetukan Peraturan Daerah Yang Berkualitas di Pemerintah Daerah - Tanggono, Claustantianus Wibisono; Sudarmanto, Kukuh; Junaidi, Muhammad; Arifin, Zaenal (Journal Juridisch, 2023)
This research aims to analyze the mechanisms for forming regional regulations carried out by regional regulation forming institutions. to produce quality regional legal products. Analyze the mechanisms that should place importance on the formation of quality regional legal products. Many regional regulations that are problematic and canceled are influenced by many factors, including political and social. To obtain a quality legal product, it requires an understanding of the mechanisms for forming good regulations that are in line with the state's goal, namely to improve the welfare of society. This research provides an understanding of the mechanism for forming quality regional regulations so that it can be a solution so that the resulting regional regulations do not conflict with the norms determined by the Government. The research method used is normative juridical which provides an overview, systematic and mechanism regarding everything related to the stages of forming quality regional regulations. By describing the applicable laws and regulations relating to the mechanism for forming regional legal products. The mechanism for forming regional regulations carried out by regional regulation forming institutions to produce quality regional legal products does not fully involve the community at every stage. The mechanism that should be in forming quality regional legal products with community participation at each stage of regional regulation formation is according to community needs. Penelitian ini bertujuan menganalisis mekanisme pembentukan peraturan daerah yang dilakukan oleh lembaga pembentuk peraturan daerah. untuk menghasilkan produk hukum daerah yang berkualitas. Menganalisis mekanisme yang seharusnya dalam menempatkan pentingnya pembentukan produk hukum daerah yang berkualitas. Banyak peraturan daerah yang bermasalah dan dibatalkan sangat dipengaruhi banyak faktor antara lain politik dan sosial. Untuk mendapatkan suatu produk hukum yang berkualitas, dibutuhkan pemahaman terhadap mekanisme pembentukan peraturan yang baik dan sesuai dengan tujuan negara yaitu menyejahterakan masyarakat. Dalam penelitian ini memberikan pemahaman mekanisme pembentukan peraturan daerah yang berkualitas sehingga dapat menjadi solusi agar peraturan daerah yang dihasilkan tidak bertentangan dengan norma-norma yang telah ditentukan oleh Pemerintah. Metode penelitian yang digunakan adalah yuridis normatif yang memberikan gambaran, sistematis, dan mekanisme mengenai segala sesuatu yang berhubungan dengan tahapan pembentukan peraturan daerah yang berkualitas. Dengan menggambarkan peraturan perundang-undangan yang berlaku berkaitan dengan mekanisme pembentukan produk hukum daerah. Mekanisme pembentukan peraturan daerah yang dilakukan oleh lembaga pembentuk peraturan daerah untuk menghasilkan produk hukum daerah yang berkualitas belum sepenuhnya melibatkan masyarakat dalam setiap tahapannya. Mekanisme yang seharusnya dalam pembentukan produk hukum daerah yang berkualitas dengan partisipasi masyarakat setiap tahapan pembentukan Perda sesuai kebutuhan masyarakat.